Should Omnichannel Customer Service Be the Same in Each Channel? - Roman DOMANSKI; Michał ADAMCZAK (Communications of International Proceedings, 2021)
Under Omnichannel Conditions, Consumers Should Not Experience Differences In The Level Of The Offer And Service Regardless Of The Channel Used To Make A Purchase. The Aim Of The Article Is To Identify Consumer Choices In The Omnichannel Together With The Assessment Of The Level Of Service Offered. As Part Of The Theoretical Part, A Systematic Literature Review Based On The Scopus Database Of Scientific Papers Was Done (729 Articles In Total). In The Practical Part, A Survey Based On An Original Research Approach Was Conducted On A Sample Of 188 Respondents And The Analysis Of The Results Included Quantity Tables, Testing The Normality Of Distribution Using The Anderson-Darling Method And Testing The Hypotheses By Means Of Mood's Median Test. The Survey Shows That Young Consumers Are Eager To Take Advantage Of The Possibilities Offered By Omnichannel. They Check Conditions In Many Channels And Mostly Make Rational Purchasing Decisions By Choosing The Channel With The Most Favourable Conditions. The Conducted Research Allowed To State That The Most Favourable Conditions Were Offered In Online Stores. The Results Of The Study Provide Knowledge About Customers’ Preferred Behaviour In The Environment Of Supplier Multiple Distribution Channels - Tips For Suppliers As To Which Distribution Channels Work And Whether The Offer In Them Should Be Improved Or Not.
Keywords: Omni-Channel; Service Level; Marketing Mix; Distribution Channel; Purchase; Customer Behaviour